A GLOBAL OUTLOOK ON PERMISSIBILITY (ḤALĀL) AND IMPERSIBBILITY (ḤARĀM) ACCORDING TO TAWḤĪD AND SHARIAH - Choudhury, Masudul Alam (Jurnal Syariah, 2022)
This paper presents a critical outlook of Shariah in contrast to the upholding of tawḥīd as the foundational law of unity of knowledge in the whole of Islamic study of the socio-scientific details and generality. Such a study leads us to widen the scope of Shariah, explained in accordance with the Qur’an, as the way arising from tawḥīd and returning back to tawḥīd as law in an analytical erudition of the ontological and epistemological nature of the world-system (‘ālamīn). Thereby, the treatment of permissibility (ḥalāl) and impermissibility (ḥarām), so often clamored in Shariah, is given a wide conceptual and applied meaning within the ontological and epistemological nature of this study. Several of the Shariah implications in economy, science and society are thereby critically examined by the methodological worldview of tawḥīd as law of unity of knowledge and the pervasively complementary nature of the socio-scientific world-system this builds.